2019
DOI: 10.1109/access.2019.2916996
|View full text |Cite
|
Sign up to set email alerts
|

Latent: A Flexible Data Collection Tool to Research Human Behavior in the Context of Web Navigation

Abstract: Internet usage has grown dramatically since the early years of its inception. The rich field of data provided by internet users in interaction with digital media content can provide insight into web-based navigation behavior and underlying psychological dimensions. Human-computer interaction in the web is an underutilized source of data for understanding human online behavior. While researchers and usability testing services do use these sources to analyze human behavior and user experience, access to the dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Behavioural features, namely, Human–Computer Interaction (HCI) features were continuously extracted using Latent, a Chrome extension to track these features in the context of web-based navigation [ 31 ]. Mouse tracking, keyboard strokes, audio, snapshots, and screenshots were recorded and stored in a MongoDB for future analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioural features, namely, Human–Computer Interaction (HCI) features were continuously extracted using Latent, a Chrome extension to track these features in the context of web-based navigation [ 31 ]. Mouse tracking, keyboard strokes, audio, snapshots, and screenshots were recorded and stored in a MongoDB for future analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Latent is a chrome extension used to track the HCI in contexts of web-based navigation [35]. This tool monitors and collects data of the mouse movement, keyboard presses, screenshots, audio, and snapshots using the computer's webcam during the Python tutorial, which involves extensive interaction with the computer.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…A study by psychologist Mehrabian revealed that language only accounts for 7% of the information expressed in interpersonal interactions, whereas facial expressions express as much as 55%. This suggests that facial expressions play a significant role in human emotion judgment [1] and can be applied in a variety of scenarios, including medical treatment [2,3], fatigue driving detection [4][5][6][7], social robots [8][9][10], and other human-computer interaction systems [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%